2004
DOI: 10.1111/j.1471-0528.2005.00306.x
|View full text |Cite
|
Sign up to set email alerts
|

Uterus and bladder necrosis after uterine artery embolisation for postpartum haemorrhage

Abstract: a Case reportA 32 year old primipara was admitted for premature rupture of the membranes at 37 weeks of gestation. She had a history of miscarriage with curettage in association with previous pregnancy. She delivered a healthy male child. After manual delivery of the placenta, exploration of the uterus and oxytocin was required to control bleeding. Selective uterine artery embolisation was carried out because there was an adherent placental cotyledon in the left uterine horn causing uncontrollable bleeding.Sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(50 citation statements)
references
References 14 publications
(27 reference statements)
1
42
0
7
Order By: Relevance
“…Infrequently, complications such as ischaemia of the bladder and uterus have also been reported. 38 A systematic review estimated a success (avoidance of hysterectomy) rate of around 92% with uterine compression sutures, 91% after arterial embolisation, 84% after balloon tamponade, and 85% after iliac artery ligation or uterine devascularisation. 6 Randomised controlled trials of these treatment options would be difficult to perform in such life-threatening emergencies.…”
Section: Discussionmentioning
confidence: 99%
“…Infrequently, complications such as ischaemia of the bladder and uterus have also been reported. 38 A systematic review estimated a success (avoidance of hysterectomy) rate of around 92% with uterine compression sutures, 91% after arterial embolisation, 84% after balloon tamponade, and 85% after iliac artery ligation or uterine devascularisation. 6 Randomised controlled trials of these treatment options would be difficult to perform in such life-threatening emergencies.…”
Section: Discussionmentioning
confidence: 99%
“…Intrauterine synechia may be related to endometrial ischaemia secondary to embolisation. Indeed, uterine necrosis following the isolated use of 45-150-lm 35 and 200-500-lm 36 polyvinyl alcohol particles and gelfoam pledgets, 37 or the combined use of gelfoam pledgets and 150-250-lm polyvinyl alcohol particles, 38 has been reported previously. Moreover, an experimental animal study on ewes found that polyvinyl alcohol particles were associated with more intense uterine necrosis than were calibrated microspheres, and uterine necrosis occurred more frequently with small rather than large polyvinyl alcohol particles and microspheres.…”
Section: Discussionmentioning
confidence: 99%
“…Retroperitoneal hemorrhage, endometritis, endometrial infection, vaginal necrosis, bladder necrosis, limb ischemia, muscle necrosis, cardiac pulmonary edema due to massive hemorrhage, transient renal failure. c. Permanent adverse sequelae [13,30,[32][33][34]. Uterine necrosis, vaginal fistula, Asherman syndrome.…”
Section: Specific Commentsmentioning
confidence: 99%